Promoting Employee Organizational Citizenship Behavior (OCB) in Small- and Medium-Sized Enterprises: A Cognitive and Affective Perspective on Ethical Leadership - Wei Su; Juhee Hahn (Behavioral Sciences)
Compared to the formal rules and regulations of large companies, leadership behavior has a greater influence on employee behaviors in small and medium enterprises (SMEs). Unlike large enterprises, many SMEs have a weaker market position, and their survival and development depend on employees’ willingness to make additional efforts beyond their formal job duties. Thus, this study focuses on SME employees to explore the effect of ethical leadership on subordinates’ organizational citizenship behavior (OCB). This study proposes a multilevel mediating model, where ethical climate and ethical role modeling represent cognitive social learning perspectives at the team and individual levels, respectively, while affective well-being serves as an individual-level affective perspective. A total of 426 valid questionnaires from 71 teams were collected, and MPLUS was used to verify the study hypotheses. The results indicate that (1) ethical leadership has a significant positive impact on employee OCB; (2) ethical leadership also significantly affects team ethical climate, ethical role modeling, and affective well-being; and (3) the partial mediating effects of team ethical climate, ethical role modeling, and affective well-being are confirmed. This research provides empirical evidence for the mechanism between ethical leadership and employee OCB in SMEs.